Referral patterns and outcomes of a highly specialised pelvic exenteration multidisciplinary team meeting: A retrospective cohort study. Issue 6 (June 2020) - O'Shannassy, Sarah J.; Brown, Kilian G.M.; Steffens, Daniel; Solomon, Michael J.
Abstract: Introduction: The purpose of this study was to review recommendations made from a specialist pelvic exenteration (PE) multidisciplinary team (MDT) and to provide insights as to the impact of the MDT on patient selection and clinical decision making. Materials & methods: A retrospective review was conducted at Royal Prince Alfred Hospital's PE MDT between June 2014 and December 2015. Data was collected from the recorded minutes of MDT meetings. Referral information and clinical data was extracted from individual patient files. Additional data including operative dates and surgical resection margins were collected from electronic medical records. Results: Of the 183 patients considered for PE during the MDT meeting, 104 (57%) were recommended for surgery. Factors that influenced the recommendation in favour of surgery were referral by a surgeon (P = 0.004), referral from a rural location (P = 0.05) and having locally advanced primary cancer (P < 0.001). Patients who were seen by the unit's surgeon prior to the MDT did not impact on the MDT recommendation nor the decision for or against surgery (P = 0.771). The most common reason for recommendation against PE was unresectable distant metastatic disease (43%). Conclusions: The PE MDT meeting is a critical step in the patient care pathway and facilitates critical decision making. Anatomically-based contraindications to surgery (i.e. involvement of adjacent organs, bone and neurovascular structures) do not appear to influence MDT decision making regarding resectability.